Strike Season ? - Pia Stalder (Recherches en didactique des langues et des cultures)
This article focuses on the subject of intercultural management in international meetings at work. It is structured as follows : the author starts with an overview of communication practices and strategies that can be observed in international teams facing linguistic, cultural and social diversity. Then she looks at the competencies of the "actors on the international stage" : what kind of knowledge and knowhow do they need in order to "play" their roles ? Finally, the author presents several training methods aiming at the development of intercultural competences of (future) actors on the international stage. An anecdote2 in four Acts, which is illustrative of the subjects discussed, is inserted in the article.